Comparative Study On The Perfomance Of RRII 105 Under High And Low Density Planting In Chirayinkeezh Taluk - Abdul Hameed A (Department of Plantation Crops and Spices, College of Horticulture, 1996)
With a view to evaluate the performance of RRII 105 under different planting densities, 25 villages in Chirayinkeezh taluk of Thiruvananthapuram district were selected covering an area of 1915 hectares. Fifty units selected were categorized into three groups based on the number of plants per hectare. Group one comprised of those with 450 to 500 trees per hectare; group two, 501-600 trees per hectare and group three, above 600 trees per hectare. The holdings selected were planted during 1985 and 1990. Observations pertaining to growth, yield, incidence of diseases, wind damage, brown bast, etc. were recorded by periodical visit to the holdings as well as from the records maintained in the Regional Office, Rubber Board. The results of the present study generally agree with the results of experiments reported earlier. It is a fact that plants under wider spacing will be vigorously growing and is likely to attain tappable girth comparatively earlier. At lower densities, per tree yield is higher but the per hectare yield is low when compared to high densities of planting. The effect of close planting can be seen in the net income from a unit area of rubber plantation. Though the per tree yield is low in medium and high densities of planting, the total net income is always high. The high density also leads to high cost of maintenance. For meeting the tapping charge alone. Over 45 per cent of the maintenance cost is to be set apart. This item of expenditure goes upto 50 per cent in highest densities of plantation. The general notion is that if family labour is employed, the closer plantings will be more profitable as there is considerable savings towards labour cost. The peculiarity observed in Chirayinkeezh taluk is that even the smallest units measuring around 0.20 hectare in extent are engaging paid tappers and estate workers. This is because no grower is entirely dependent on rubber or agriculture in particular as a sole source of income. Under the circumstances it is advisable to recommend an initial stand between 550-600 per hectare subsequently reduced to 500 hectare at the time of tapping for small holders of Chirayinkeezh taluk as there is not much difference between the stand groups of 450-500 and 501-600 per hectare with respect to yield, net return and on various growth parameters. Keeping in view the recommendation in Malaysia (750 per hectare for small holders), it is suggested to undertake in depth studies in this direction before giving a specific recommendation with regard to high density planting considering the unique local situations. The findings of the study can be summarized as follows: Generally, plants in lower planting densities had medium to dense canopy Plants under wider spacing were comparatively more vigorous Height of branching was at higher level in close planting The intensity of common diseases affecting rubber tree could be rated as ‘low’ and large scale preventive/remedial measures were not warranted Daily tapping was the common accepted system of tapping in small holdings Brown bast symptoms started appearing notably and would intensify in the coming years Though per hectare yield was positively correlated with planting density, the per tree yield recorded a negative correlation. Higher BCR (2.28) was recorded in the case of normal planting density (450-500 trees/ha).